Attitude, aptitude, ability and autonomy: The emergence of 'offroaders', a special class of nomadic worker - Harmer BM; Pauleen DJ (Taylor & Francis Group, 2012)
Freedom to choose when, where and on what to work might be viewed as mere telework. However, when we mix the adoption of ubiquitous technologies with personalities that take pleasure in problem solving and achievement for its own sake, a strong need for autonomy, the freedom to work wherever and whenever the mood strikes, and add a dash of entrepreneurial spirit, then perhaps we are seeing an emergent class of worker, and even the possibility of new organisational forms. This research draws on adaptive structuration theory to search for evidence of a different way of working, hidden among otherwise familiar patterns. It concludes by considering what implications the employment of such individuals might have for management processes with organisations.
This is an electronic version of an article published in Harmer, B. M., & Pauleen, D. J. (2010). Attitude, aptitude, ability and autonomy: the emergence of ‘offroaders’, a special class of nomadic worker. Behaviour & Information Technology, 1-13. http://dx.doi.org/10.1080/0144929x.2010.489117 Behaviour & Information Technology is available online at: www.tandfonline.com
Keywords: Joy of use; ICT; Cognitive absorption; Individualisation; Universal access